Freeze-all embryos during treatment with assisted reproduction: Health economic aspects. (February 2023) - Venetis, Christos; Keller, Elena; Chambers, Georgina M.
Abstract: Assisted reproductive technologies are evolving, with the most recent example being the introduction of the freeze-all policy during which a fresh embryo transfer does not take place and all embryos of good quality are cryopreserved to be used in future frozen embryo transfers. As the freeze-all policy is becoming more prevalent, it is important to review the economic aspects of this approach, along with considerations of efficacy and safety, and the role of emerging freeze-all-specific ovarian stimulation strategies. Based on the available evidence, the freeze-all policy presents distinct clinical advantages, particularly for high responders. Available health economic evaluations are limited. Two good-quality cost-effectiveness analyses based on randomized controlled trials suggest that the freeze-all strategy is unlikely to be cost-effective in non-polycystic ovarian syndrome (non-PCOS), normally responding patients. However, the cost-effectiveness of the freeze-all strategy in different populations of patients and in different settings has not been evaluated, nor has the clinical and economic efficacy of modern freeze-all-specific ovarian stimulation protocols that are likely to simplify treatment and make it more affordable for patients. Economic evaluations that incorporate good practice health technology assessment (HTA) methods are needed to compare freeze-all with conventional embryo transfer strategies. Furthermore, future research should address the unique limitation of traditional HTA methods in valuing a life conceived through fertility treatment. Highlights: The freeze-all policy is becoming increasingly popular as cryopreservation technologies have improved. Available evidence suggests that freeze-all is likely to be associated with increased efficacy in high responders and increased safety both in high and normal responders. Based on a small number of recent studies, evidence suggests that the freeze-all policy is unlikely to be cost-effective in non-PCOS normally responding patients. High-quality cost-effectiveness analyses (performed by health economists in conjunction with clinicians and funding bodies) are needed in patients at risk of OHSS, PCOS, and high responders.